(untitled) (Stavební obzor - Civil Engineering Journal, 2018)
In recent years, algae bloom phenomenon outbreaks frequently in large-scale water bodies during summer. At present, mechanical method is used to collect cyanobacteria and reduce volume. However, the characteristics of algae, namely high viscosity, small particle size and high moisture content, lead to poor efficiency of dehydration. In order to improve the dehydration efficiency of algae and achieve the purpose of volume reduction and dehydration, the dehydration performance of Microcystis aeruginosa was studied in this paper. Three filter aid agent, including Poly Aluminium Chloride (PAC), Montmorillonite and Diatomite were added to the algae solution to improve filterability of Microcystis aeruginosa. The results showed that all of three filter aid agent have positive effect on the algae filtration rate, specific resistance, compression index and dehydration efficiency. Compared with the other two filter aid agents, the filtration rate of Diatomite is relatively faster. Meanwhile dehydration performance is better as well. When the dosage of Diatomite was 10.0g/L, the filtration rate increased from 0.108 L/h to 0.504 L/h. In addition, the compression index was reduced from 0.710 to 0.594. The specific resistance was reduced from 7.62 × 1010 s2/g to 2.35 × 108 s2 /g while the water content was decreased from 86.5% to 66.4%.